Distribution of the Ixodid Tick Hyalomma marginatum (Acari, Ixodidae) in Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2011)
The Northern boundary of the current distribution range of Hyalomma marginatum Koch in Ukraine that passes along the North of Odesa, Mykolayiv, Kirovograd, Dnipropetrovsk, Zaporizhia, Donetsk and Luhansk Oblasts has been specified. The natural habitat is mapped according to different possibilities for mass reproduction. Regular findings of H. marginatum inhabited unusual places may contribute to the spreading of diseases dangerous to humans and animals to new areas, where the latter may be treated as a biological threat of large epidemics and epizootics. Natural habitat of the Ixodidae species has been mapped in consideration of feeding types and the ability of it hosts to travel. Only the areas where all stages are regularly found were included what corroborates Ixodidae species establishing in new areas. Уточнена северная граница современного ареала Hyalomma marginatum на территории Украины, которая проходит по северу Одесской, Николаевской, Кировоградской, Днепро петров ской, Запорожской, Донецкой и Луганской областей. Представлена карта с дифференцированным по возможности массовых размножений ареалом. Регулярные находки H. marginatum на несвойственных местах проживания играют роль в распространении возбудителей болезней опасных для человека и животных на новые территории, где последние могут представлять угрозу широких эпидемий и эпизоотий. Составлена карта ареала этого иксодового клеща с учетом типа питания и возможности хозяев к перемещению. В него включены только территории, где периодически находили все стадии развития, чем подтверждено укоренение вида на новых участках.